Effect of replanting systems on populations of strategus aloeus (l.) and rhynchophorus palmarum (l.) associated with the oil palm oxg interspecific hybrid (elaeis oleifera × elaeis guineensis) in southwestern colombia (2014)
The oil palm replanting process produces a large amount of organic matter that, as it begins to decompose, becomes a breeding ground for various pests, including Strategus aloeus and Rhynchophorus palmarum. Different crop replanting systems are being used today. The method used depends on the plantation and it is basically associated with the costs involved in the process. However, sometimes too little attention is paid to other issues related to the new crop, such as plant health and agronomic management. This study evaluated the effect of different crop replanting alternatives in relation to two pest populations affecting oil palm plantations. Pest populations of S. aloeus and R. palmarum were assessed and monitored for 27 months using seven replanting methods. It was found that the largest number of individuals of R. palmarum and S. aloeus was associated with the stem felling and stacking method. No individuals of the two pest species were found when the felling and burying method was used. The exposed organic matter method that had the lowest number of individuals of both pest species was the felling, chipping, spreading method.